Colonial justice and the Jews of Venetian Crete - Lauer, Rena N. (Middle Ages series., 2019)
Rena N. Lauer shows how Crete's Jews turned not only to their own religious courts but also to the secular Venetian judicial system to address matters as prosaic as taxation and as dramatic as murder. In the process, Lauer contends, Venetian Jews grew more open and flexible, experiencing little of the anti-Judaism common in Western Europe.